2012
DOI: 10.1111/j.1469-8137.2012.04284.x
|View full text |Cite
|
Sign up to set email alerts
|

The composition of phyllosphere fungal assemblages of European beech (Fagus sylvatica) varies significantly along an elevation gradient

Abstract: SummaryLittle is known about the potential effect of climate warming on phyllosphere fungi, despite their important impact on the dynamics and diversity of plant communities. The structure of phyllosphere fungal assemblages along elevation gradients may provide information about this potential effect, because elevation gradients correspond to temperature gradients over short geographic distances.We thus investigated variations in the composition of fungal assemblages inhabiting the phyllosphere of European bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
141
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 73 publications
12
141
0
Order By: Relevance
“…Recently, it was shown that the composition of leaf-associated fungi on F. sylvatica is correlated primarily with the annual mean temperature (Cordier et al 2012, Coince et al 2014. In the present work, the detection B. nummularia DNA in symptomless tissue of beech showed a significant decreasing trend as the mean precipitation of the month preceding the sampling increases (R 2 = 0.86), i.e., the amount of latent infection increased with decreasing precipitation.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, it was shown that the composition of leaf-associated fungi on F. sylvatica is correlated primarily with the annual mean temperature (Cordier et al 2012, Coince et al 2014. In the present work, the detection B. nummularia DNA in symptomless tissue of beech showed a significant decreasing trend as the mean precipitation of the month preceding the sampling increases (R 2 = 0.86), i.e., the amount of latent infection increased with decreasing precipitation.…”
Section: Discussionsupporting
confidence: 49%
“…There is already a large body of knowledge showing that the composition and structure of the tree microbiota strongly respond to environmental factors such as temperature, drought, atmospheric CO 2 , or urbanization (Jumpponen and Jones 2010;Compant et al 2010;Peñuelas et al 2012;Cordier et al 2012a;Coince et al 2014;Rico et al 2014). There is also increasing evidence showing that the tree microbiota is influenced by the genetic variability of trees, both at intraspecific (Schweitzer et al 2008;Cordier et al 2012b;Bálint et al 2013) and interspecific (Knief et al 2010;Redford et al 2010;Kembel and Mueller 2014;) levels.…”
Section: Hyperparasitism Of Fungal Pathogens: a Poorly Understood Butmentioning
confidence: 99%
“…Pathogens themselves host a diversity of parasites, especially mycoviruses ( Witzell et al 2014). Some experimental manipulations at small spatial scales have highlighted the role of microbial communities in disease control (Arnold et al 2003;Matos et al 2005), while observations at larger scales have revealed environmental factors driving these communities (Cordier et al 2012a;Peñuelas et al 2012). Both approaches are required to predict, and ultimately manage, microbial interactions and functions in the context of global change (Kinkel et al 2011;Berlec 2012;Borer et al 2013;Lebeis 2014;VayssierTaussat et al 2014;Hacquard and Schadt 2015).…”
Section: Conclusion and Recommendations For The Futurementioning
confidence: 99%
“…Another selective filter is the environment. Gradients of elevation (17), temperature, and rainfall (18) as well as variations in soil nutrient content (19) have all been associated with changes in aboveground fungal assemblage. In temperate regions, even seasonal thermal fluctuations have been shown to affect the dynamics of plant pathogens (20,21).…”
mentioning
confidence: 99%